2022
DOI: 10.17223/17267080/84/7
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Predictors of Early Access for a Doctor among Women with Primary Luminal Breast Cancer

Abstract: Introduction. One of the most common localizations where there is a connection between early diagnosis, timely treatment and a successful outcome of a disease is breast cancer. The behavior of a woman is associated with whether she is seeking medical help earlier or later, this now is for the first time determined, among other things, by a number of psychological characteristics of her personality. These can be cognitive beliefs included in her picture of the world, locus of control, resilience, and life orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our 2019-2021 study identified psychological characteristics of women with breast cancer that act as predictors of early or late initial healthcare seeking (Tsiring et al, 2022;Tsiring et al, 2021a;Tsiring et al, 2021b). The subjects were women with different stages of breast cancer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our 2019-2021 study identified psychological characteristics of women with breast cancer that act as predictors of early or late initial healthcare seeking (Tsiring et al, 2022;Tsiring et al, 2021a;Tsiring et al, 2021b). The subjects were women with different stages of breast cancer.…”
Section: Literature Reviewmentioning
confidence: 99%